2014
DOI: 10.1130/g35922.1
|View full text |Cite
|
Sign up to set email alerts
|

Fossil evidence of iron-oxidizing chemolithotrophy linked to phosphogenesis in the wake of the Great Oxidation Event

Abstract: The oxygenation of Earth's atmosphere allowed for the diversification of metabolisms to include those that rely on oxygen and its derivatives. For example, chemolithotrophic oxidation of sulfide and iron both require oxygen or nitrate as terminal electron acceptors. A growing number of oxygen-utilizing chemolithotrophs are known to accumulate intracellular polyphosphate as an energy reserve that allows them to adapt to the fluctuating redox conditions in their distinctive-gradient habitats. Polyphosphate is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…A similar range of δ 13 C org values measured in situ on cyanobacteria‐like Proterozoic microfossils have been interpreted similarly (Williford et al ., ). This does not exclude possible contributions from some phototrophic Fe(II)‐oxidizing bacteria (Crosby et al ., ), which are known to live in the photic zone of modern rift lakes (Crowe et al ., ). There is also the likely possibility that anoxygenic phototrophic micro‐organisms participated in the formation of these stromatolites, as they have been reported from modern stromatolites (Papineau et al ., ; Bosak et al ., ; Goh et al ., ; Birgel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar range of δ 13 C org values measured in situ on cyanobacteria‐like Proterozoic microfossils have been interpreted similarly (Williford et al ., ). This does not exclude possible contributions from some phototrophic Fe(II)‐oxidizing bacteria (Crosby et al ., ), which are known to live in the photic zone of modern rift lakes (Crowe et al ., ). There is also the likely possibility that anoxygenic phototrophic micro‐organisms participated in the formation of these stromatolites, as they have been reported from modern stromatolites (Papineau et al ., ; Bosak et al ., ; Goh et al ., ; Birgel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stalk-like morphologies have been observed in the rock record (Hofmann & Farmer, 2000;Little et al, 2004;Slack et al, 2007), although stalks have not yet been observed in BIFs. However, stalks may be preserved in special cases, in particular when quickly encased in silica, carbonate, or phosphate, for example, in association with stromatolites (Crosby et al, 2014). However, stalks may be preserved in special cases, in particular when quickly encased in silica, carbonate, or phosphate, for example, in association with stromatolites (Crosby et al, 2014).…”
Section: Fe Microbial Matsmentioning
confidence: 99%
“…In a similar manner, large marine sulfur-oxidizing bacteria in the family Beggiatoaceae also store poly-P, and have been shown to hydrolyze their poly-P stores upon exposure to anoxic or sulfidic conditions (Schulz and Schulz, 2005; Brock and Schulz-Vogt, 2011). Poly-P hydrolysis by large sulfur-oxidizing bacteria has been implicated in phosphate mineral formation in seasonally anoxic upwelling zones through the supersaturation of sediment pore waters, and might constitute an important sink in the global P cycle, both in modern sediments (Schulz and Schulz, 2005;Goldhammer et al, 2010;Brock and Schulz-Vogt, 2011) and in the past (Bailey et al, 2013;Crosby et al, 2014).However, marine microbial communities are diverse, and beyond studies of large sulfuroxidizing bacteria, little is known about the diversity and activity of poly-P utilizing microbes in marine sediments that experience fluctuating redox conditions. Therefore, we used a metatranscriptomic approach to compare the expression of poly-Prelated genes in sediments that were experimentally exposed to anoxic and oxygenated conditions.…”
mentioning
confidence: 99%